Reconstruction of the tumor spatial microenvironment along the malignant-boundary-nonmalignant axis - Zhenzhen Xun; Xinyu Ding; Yao Zhang; Benyan Zhang; Shujing Lai; Duowu Zou; Junke Zheng; Guoqiang Chen; Bing Su; Leng Han; Youqiong Ye (Nature Communications, 2023)
Delineating the cellular composition of tumour boundaries in spatial transcriptomics (ST) data is challenging. Here, the authors develop Cottrazm to integrate ST with histological imaging and single-cell data, identify the malignant and non-malignant tissue boundaries, deconvolute cell-type composition, and reconstruct cell type-specific gene expression profiles.